Macroeconomic Determinants of Accumulated M&A Transaction Values within the U.S. Market - I. V. Tregub; A. F. Butyrskiy (Управленческие науки, 2023)
The corporate wisdom propounds mergers and acquisitions (M&A) as a notable strategy for extensive (non-organic) growth in the market and, as a result, gaining financial advantage and strategic superiority and ascendancy along the way. Hence, this instrument undeniably occupies the highest ranks of instruments for corporate management. Considering all aforementioned, the work object is to research to which extend the macroeconomic indicators have an effect on the annually aggregated volume of mergers and acquisitions, entered within the United States of America in the historical period of 1985–2021. The subject of the study is defined as U.S. mergers and acquisitions market. By employing the ordinary least square method of a multiple linear regression equation, it was determined that logarithmic GDP growth together with the discount rate had a significant positive effect on the explanation of the dependent variable, while the 10-year US Treasury bond yield had a negative relationship. Further, several statistical tests were conducted to ensure the authenticity of results obtained and potential for utilization of the model for the purpose of estimation forward values. The practical significance of the research is recognized as uncovering econometric model for the purpose of forecasting mergers and acquisitions volumes, resulting in effective corporate management decisions with regard to timing and market sentiment.